2006
DOI: 10.1200/jco.2006.24.18_suppl.10606
|View full text |Cite
|
Sign up to set email alerts
|

Impact of taxanes on weight gain during neoadjuvant chemotherapy (Ctx) for breast cancer (BC)

Abstract: 10606 Background: Weight gain after the diagnosis of BC has been associated with increased risk of recurrence and mortality. Previous studies have documented weight gain after cyclophosphamide, methotrexate, and 5-fluoruracil (CMF) and adriamycin and cyclophosphamide (AC) chemotherapy, but the impact of taxane chemotherapy has not been described. Methods: We reviewed the charts of 119 patients (pts) who completed neoadjuvant Ctx between 1997–2005. Age, baseline body mass index (BMI), tumor size, nodal status,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Furthermore, a higher number of taxane-based chemotherapy cycles (mean: 3.89±1.11 cycles) was significantly associated with weight gain. Another study evaluated 119 patients who completed neoadjuvant chemotherapy with at least two years of follow-up (median: 26.3 months) and revealed that, among 97 patients who received anthracycline followed by taxane, the mean weight changes were -0.8 kg after anthracycline and +3.2kg after taxane [23], which are similar to our results. Another multicenter retrospective study (2001-2010) revealed that treatment using anthracycline plus taxane was associated with more weight gain (+0.9kg) relative to anthracycline alone, which the authors attributed to the longer duration of the combination treatment [24].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, a higher number of taxane-based chemotherapy cycles (mean: 3.89±1.11 cycles) was significantly associated with weight gain. Another study evaluated 119 patients who completed neoadjuvant chemotherapy with at least two years of follow-up (median: 26.3 months) and revealed that, among 97 patients who received anthracycline followed by taxane, the mean weight changes were -0.8 kg after anthracycline and +3.2kg after taxane [23], which are similar to our results. Another multicenter retrospective study (2001-2010) revealed that treatment using anthracycline plus taxane was associated with more weight gain (+0.9kg) relative to anthracycline alone, which the authors attributed to the longer duration of the combination treatment [24].…”
Section: Discussionsupporting
confidence: 87%
“…Since this high dose corticosteroid premedication regimen is often continued through prolonged treatment courses of weekly taxanes, Cushingoid changes, weight-gain, and other complications that arise in a dose-dependent fashion have been reported. 10 Other dose-dependent adverse effects of steroids may include flushing, acne, hyperglycemia, hypertension, epigastric distress or dyspepsia, weight gain, edema, perineal pruritus, anxiety, agitation, depression, hiccups, insomnia, increased appetite, metabolic abnormalities, mood changes, oral candidiasis, and infections. Prolonged treatment may increase the risk of osteoporosis, osteonecrosis, myopathy, glaucoma, cataracts, and impaired wound healing.…”
Section: Introductionmentioning
confidence: 99%